SOSIALISASI PEMILU 2024 YANG BERSIH, JUJUR, SEHAT, DAN ADIL DI DESA PEMOGAN - Satya Wiryani, Ni Putu; Sariani, Ni Luh Putu; Arniti, Ni Ketut (Politeknik Negeri Sriwijaya, 2024)
This service aims to provide effective and inclusive outreach about the 2024 Election in Pemogan Village, with a focus on cleanliness, honesty, health and justice in the election process. The methods used include observation, interviews, socialization and evaluation. The results of the service show that there is a great need for comprehensive and easily accessible socialization about the 2024 Election. It was also found that it is important to ensure cleanliness, honesty, health and fairness in all stages of the election process to ensure fair and transparent participation. The results of the service show a significant increase in the Clean, Honest, Healthy and Fair aspects of the 2024 Election activities in Pemogan Village. The percentage of environmental cleanliness and election holding increased from 50% to 75%, integrity and honesty in the election process also increased significantly, reaching 75% of the participation of Pemogan Village residents. Apart from that, awareness of the importance of health and equality in access to political information has also experienced a satisfactory increase, showing the effectiveness of the socialization strategy that has been carried out.